The Effect of Ornamental Plants on Reducing the Intensity of Electromagnetic Wave Radiation - Lestari, Mugi; Sulhadi, Sulhadi; Sutikno, Sutikno (Universitas Negeri Semarang, 2023)
Entering the digital era, the culture of human life is increasingly inseparable from the use of electromagnetic waves which are very useful in supporting human life, but in the other side, it also has negative impacts in the form of radiation that threatens human health. Only few people realize that ornamental plants have many benefits other than as a decoration inside or outside the room. Several types of ornamental plants have the ability to absorb electromagnetic radiation emitted by electronic equipment. In this simple physics research, measurements were made to compare the absorption of several types of ornamental plants to electromagnetic wave radiation, those are karet kebo, betel, succulent, ivy plant, and snake plant. The research results show that snake plant’s ability to absorb electromagnetic wave radiation is the greatest than others. Research conducted on ivy shows that the absorption of ornamental plants to electromagnetic wave radiation is influenced by the distance of the plant to the radiation source, where the closer the distance between the ornamental plants to the source of electromagnetic wave radiation is, the greater the absorption of radiation occurs, resulting in a decrease in the intensity of electromagnetic radiation also getting bigger. The trend of changes in the absorption of electromagnetic wave radiation shows a decrease in each increase in distance according to the exponential graph.